Markedly Deranged Injury Site Metabolism and Impaired Functional Recovery in Acute Spinal Cord Injury Patients With Fever. Issue 7 (July 2018) - Gallagher, Mathew J.; Zoumprouli, Argyro; Phang, Isaac; Schwab, Jan M.; Kopp, Marcel A.; Liebscher, Thomas; Papadopoulos, Marios C.; Saadoun, Samira
Abstract : Objectives: To characterize the effect of fever after acute, traumatic spinal cord injury on injury site metabolism and patient outcome. Design: Longitudinal cohort study. In 44 patients (London cohort), we determined the effect of fever on intrathecal injury site metabolism by analyzing 1, 767 hours of intraspinal pressure and 759 hours of microdialysis data. We also determined the effect of fever burden, computed for the first 2 weeks in hospital, on neurologic outcome. A distinct cohort of 33 patients (Berlin cohort) was used to independently validate the effect of fever burden on outcome. Setting: ICUs in London and Berlin. Patients: Seventy-seven patients with acute, traumatic spinal cord injuries. Interventions: In the London patients, a pressure probe and a microdialysis catheter were placed intradurally on the surface of the injured cord for up to a week. Measurements and Main Results: Fever (> 37.5°C) occurs frequently (37% of the time) after spinal cord injury. High-grade fever (≥ 38°C) was associated with significantly more deranged metabolite levels than normothermia (36.5–37.5°C), that is, lower tissue glucose (median 2.0 vs 3.3 mM), higher lactate (7.8 vs 5.4 mM), higher glutamate (7.8 vs 6.4 µM), and higher lactate-to-pyruvate ratio (38.9 vs 29.3). High-grade fever was particularly detrimental on injury site metabolism when the peripheral leukocyte count was high. In the London and Berlin cohorts, high fever burden correlated with less neurologic improvement. Conclusions: Early after spinal cord injury, fever is associated with more deranged injury site metabolism than normothermia and worse prognosis.